Symbiotic microalgae and microbes: a new frontier in saline agriculture - Ren, Cheng-Gang; Kong, Cun-Cui; Li, Si-Ming; Wang, Xiao-Jing; Yu, Xiao; Wang, Yin-Chu; Qin, Song; Cui, Hong-Li (Frontiers in Microbiology, 2025)
With the growing human population worldwide, innovative agricultural development is needed to meet food security needs. However, this has inadvertently led to problematic irrigation practices and overuse of agrochemicals. Such practices can exacerbate soil salinization, which prevents plant growth. As a progressively widespread and escalating problem, soil salinization poses a major threat to global food security. Compared with the traditional use of microalgae or microorganisms that act on plant growth, microalgae–microorganism symbiosis has significant advantages in promoting plant growth. Microalgae and microorganisms can work together to provide a wide range of nutrients required by plants, and they exhibit nutrient complementarity, which supports plant growth. Here, the development potential of microalgae–microbial symbiosis for enhancing plant salt tolerance was investigated. Our review demonstrated that the metabolic complementarity between microalgae and microorganisms can enhance plant salt tolerance. The diversity of a microalgae–microorganism symbiotic system can improve ecosystem stability and resistance and reduce the incidence of plant disease under salt stress. These systems produce bioactive substances (e.g., phytohormones) that promote plant growth, which can improve crop yield, and they can improve soil structure by increasing organic matter and improving water storage capacity and soil fertility. Exploiting the synergistic effects between microalgae and beneficial microorganisms has biotechnological applications that offer novel solutions for saline agriculture to mitigate the deleterious effects of soil salinity on plant health and yield. However, there are several implementation challenges, such as allelopathic interactions and autotoxicity. To make microalgae–bacteria consortia economically viable for agricultural applications, optimal strains and species need to be identified and strategies need to be employed to obtain sufficient biomass in a cost-effective manner. By elucidating the synergistic mechanisms, ecological stability, and resource utilization potential of microalgae–microbial symbiotic systems, this review clarifies salt stress responses and promotes the shift of saline–alkali agriculture from single bioremediation to systematic ecological engineering.